Koszty jakości w cyklu życia produktu - Sysło, Małgorzata (Quality Costs in Product Life Cycle, 2005)
Companies, which want to run their business on the global market, must make high quality products and optimize their costs. Quality costs, include prevention costs, appraisal costs, internal and external failure, are in each of phases of product life cycle. Prevention costs, which let reduce failure and appraisal costs in market phase, predominate in research and development phase.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 291-296